Manajemen Produksi pada Siaran Berita Lokal Kompas Medan di Kompas TV - Andini Nurbahri; Lola Fahira Mutahar; Suci Nabila; Muhammad Fauzan Fayrozi (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Regional autonomy provides an opportunity for several local media to play an active role in regional development or introduce social culture through local television media, which will assist the government in promoting its programs to the public. In the television media broadcasting industry, competition is basically a competition to grab the audience's attention. Therefore, the manager of a television station must have a clear plan to win the hearts of the audience. This research is a qualitative descriptive research, meaning that the researcher only describes a situation or event. The purpose of this study is to gain an understanding of the broadcast management of Kompas TV Medan. The results of the study show that in facing competition in the digital era, the management of Kompas TV Medan broadcasts has been going well. Kompas TV performs production management procedures that apply the concept of Planning, Organization, Action and Control (POAC) to news management at Kompas TV Medan, especially the news program "Kompas Sumut", to get quality local broadcasts. At this stage evaluation is also carried out as a way to manage the program.